Barriers to, and policy opportunities for, the growth of renewable energy technologies in South Africa : rethinking the role of municipalities - Tshehla, Maloba Gerard (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.